2019
DOI: 10.1103/physreve.100.042122
|View full text |Cite
|
Sign up to set email alerts
|

Solvable model of a many-filament Brownian ratchet

Abstract: We construct and exactly solve a model of an extended Brownian ratchet. The model comprises an arbitrary number of heterogeneous, growing and shrinking filaments which together move a rigid membrane by a ratchet mechanism. The model draws parallels with the dynamics of actin filament networks at the leading edge of the cell. In the model, the filaments grow and contract stochastically. The model also includes forces which derive from a potential dependent on the separation between the filaments and the membran… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…In this article, we demonstrate how even in a static, structureless environment, particles can themselves be the source of inter-particle ratcheting when they have heterogeneous properties and interact via volume exclusion. This inter-particle ratchet effect underlies correlation-phenomena found in a range of models including lattice exclusion processes with particle-wise disorder [10][11][12] or driven tracers [13,14], continuous-space single-file diffusion with random diffusivities [15][16][17] or friction [18], and a recent many-filament ratchet model [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this article, we demonstrate how even in a static, structureless environment, particles can themselves be the source of inter-particle ratcheting when they have heterogeneous properties and interact via volume exclusion. This inter-particle ratchet effect underlies correlation-phenomena found in a range of models including lattice exclusion processes with particle-wise disorder [10][11][12] or driven tracers [13,14], continuous-space single-file diffusion with random diffusivities [15][16][17] or friction [18], and a recent many-filament ratchet model [19].…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, we describe how the many-filament ratchet of Ref. [19] relates to the previous cases through a simple mapping.…”
Section: Introductionmentioning
confidence: 99%
“…However, membrane fluctuations have not yet been studied. In most studies reported in the literature [16][17][18][19][20][21][22][23], the membrane is modeled as a flat rigid surface; thus, no fluctuations are accounted for. Although the membrane fluctuations are assumed to be a Gaussian distribution of the membrane height in Ref.…”
mentioning
confidence: 99%
“…For example, actin filaments grow at the front side of crawling cells and push the membrane forward. This membrane motion has been intensively studied by Brownian ratchet theories and simulations [15][16][17][18][19][20][21][22][23][24][25][26][27].…”
mentioning
confidence: 99%
“…Two paradigmatic ratchet models, namely flashing and rocking ratchet [3,[13][14][15][16][17] models always involve an intermittent forcing to drive the system (modeled as a single particle) out of equilibrium. The work done by the system in this case is an amount of work extracted mostly from the source of directionless forcing.…”
mentioning
confidence: 99%